2021
DOI: 10.1186/s12866-021-02319-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of methicillin resistance and superantigenic toxins in Staphylococcus aureus strains isolated from patients with cancer

Abstract: Background This study aimed to determine the frequency of methicillin-resistant Staphylococcus aureus (MRSA), antibiotic resistance patterns, superantigenic toxins profile, and clonality of this pathogen in patients with cancer. Results In total, 79 (25.7%) isolates were confirmed as Staphylococcus species, from which 38 (48.1%) isolates were S. aureus, and 29 (76.3%) isolates were confirmed as MRSA. The highest resistance in MRSA strains was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Individuals harbouring MRSA, which is frequently multidrug resistant, are at risk of serious threat to themselves, and also play a role in the dissemination of the pathogen in hospital and community settings. Although the 29/307 MRSA recorded among hospitalised oncology patients examined in Ahvaz, Khuzestan Province, southwest of Iran 22 was much lower, it could not be ruled out that the higher rate observed in this study is unconnected to the antibiotic use pattern in Nigeria. 23 The isolates we examined were mostly from clinical sources and about 24% of the whole collection were from individuals who had no known indications for antibiotic use.…”
Section: Discussioncontrasting
confidence: 59%
“…Individuals harbouring MRSA, which is frequently multidrug resistant, are at risk of serious threat to themselves, and also play a role in the dissemination of the pathogen in hospital and community settings. Although the 29/307 MRSA recorded among hospitalised oncology patients examined in Ahvaz, Khuzestan Province, southwest of Iran 22 was much lower, it could not be ruled out that the higher rate observed in this study is unconnected to the antibiotic use pattern in Nigeria. 23 The isolates we examined were mostly from clinical sources and about 24% of the whole collection were from individuals who had no known indications for antibiotic use.…”
Section: Discussioncontrasting
confidence: 59%
“…Similarly, some E. coli strains can cause diarrhea and vomiting, and excessive exposure sometimes leads to kidney failure ( Money et al, 2010 ). Specific strains of S. aureus have developed resistance to multiple antibiotics ( Abbasi et al, 2021 ). The XDR S. typhi strain also shows resistance to fluoroquinolone or ceftriaxone, and its outbreak accounts for more than 20,000 cases every year ( Rasheed et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It must be emphasized that the Montazeri study was limited to cancer patients, who may have immunological disorders that could affect staphylococcal infection prevalence. 19 This result might also emphasize regional fluctuations in molecular epidemiology. The study from the Middle East showed an even more surprising result: none of the MRSA isolates expressed the eta gene, out of 76 Iraqi isolates and 49 refugee isolates.…”
Section: Discussionmentioning
confidence: 86%